PELATIHAN KOMPETENSI KEWIRAUSAHAAN PADA UKM - Nur Hidayah; Gemitalia Avisca (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2021)
Competence plays a crucial role in ensuring the sustainability of a business. The success of a business is often attributed to its ability to enhance the competence of its operations. The purpose of the PKM activities is to assist small and medium-sized enterprises (SMEs) in recognizing the significance of entrepreneurial competence in sustaining their businesses. The activity partners involved in this study are engaged in the culinary industry, specifically under the brand name "Pawon Emak," which offers a diverse range of culinary products such as nasbox snack boxes, tumpeng, birthday cakes, various market jajn, various dishes, catering services, donuts, and other pastries. Throughout the PKM activities, several challenges have been encountered, particularly in terms of improving entrepreneurial competence, which arises from partners' limited knowledge on this subject matter. Therefore, the PKM activities aim to assist partners in enhancing their understanding of entrepreneurial competence. The chosen approach for these activities is online training and socialization conducted via Zoom meetings. The training materials encompass a basic introduction to business competencies, the essential competencies required, methods for measuring entrepreneurial competencies, and other relevant topics. The results of the activities indicate that the training sessions were conducted successfully, with partners displaying enthusiasm in comprehending the presented material. Evaluation outcomes further demonstrate that the delivery of entrepreneurial competency material has effectively contributed to partners' understanding.